2021
DOI: 10.3390/nu13051593
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of the Mechanisms of β-Cell Dedifferentiation in Type 2 Diabetes

Abstract: Diabetes is a metabolic disease characterized by hyperglycemia. Over 90% of patients with diabetes have type 2 diabetes. Pancreatic β-cells are endocrine cells that produce and secrete insulin, an essential endocrine hormone that regulates blood glucose levels. Deficits in β-cell function and mass play key roles in the onset and progression of type 2 diabetes. Apoptosis has been considered as the main contributor of β-cell dysfunction and decrease in β-cell mass for a long time. However, recent studies suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 98 publications
2
18
0
Order By: Relevance
“…For example, the progression from impaired glucose tolerance (IGT) to T2D is associated with increased basal insulin, diminished first-phase glucose-stimulated insulin secretion (GSIS), and a gradual depletion of insulin stores [6][7][8]. Hyperglycemia-induced apoptosis is considered one of the major mechanisms promoting β-cell loss in T2D patients [9,10], but β-cell dedifferentiation through the loss of insulin gene expression and reactivation of progenitor markers (e.g., Ngn3, Oct4, Nanog, and L-myc) may precede β-cell death [11][12][13]. Although it is unclear whether the detrimental effects of glucotoxicity on these pathways of β-cell loss can be fully reversed, therapies that alleviate hyperglycemia, promote weight loss, and/or increase insulin sensitivity (e.g., GLP-1 receptor agonists [14], sodium-glucose co-transporter 2 inhibitors (SGLT2i) [15], thiazolidinediones (TZDs) [16], and insulin therapy [17]) have been shown to enhance markers of beta cell identity or reverse markers of β-cell dedifferentiation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the progression from impaired glucose tolerance (IGT) to T2D is associated with increased basal insulin, diminished first-phase glucose-stimulated insulin secretion (GSIS), and a gradual depletion of insulin stores [6][7][8]. Hyperglycemia-induced apoptosis is considered one of the major mechanisms promoting β-cell loss in T2D patients [9,10], but β-cell dedifferentiation through the loss of insulin gene expression and reactivation of progenitor markers (e.g., Ngn3, Oct4, Nanog, and L-myc) may precede β-cell death [11][12][13]. Although it is unclear whether the detrimental effects of glucotoxicity on these pathways of β-cell loss can be fully reversed, therapies that alleviate hyperglycemia, promote weight loss, and/or increase insulin sensitivity (e.g., GLP-1 receptor agonists [14], sodium-glucose co-transporter 2 inhibitors (SGLT2i) [15], thiazolidinediones (TZDs) [16], and insulin therapy [17]) have been shown to enhance markers of beta cell identity or reverse markers of β-cell dedifferentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Increased CysC expression may contribute directly to the pathogenesis of insulin resistance, which subsequently leads to fasting hyperglucagonemia, less early glucagon suppression and elevated postload 2-h plasma glucagon levels ( 3 , 47 , 48 ). In addition, increased CysC concentration may induce an inflammatory response by enhancing TNF-α expression ( 30 , 49 ), and inflammation may in turn lead to β-cell dedifferentiation ( 50 , 51 , 52 ), characterized by loss of β-cell identity and expression of glucagon in these β-cells ( 53 ). Moreover, our previous study has demonstrated that fatty acid-binding protein 4, an inflammatory factor primarily originated from adipose tissue, was positively associated with fasting and postprandial glucagon levels in T2D ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial β cell loss has been considered the hallmark of T2DM which even starts during the prediabetic stage [114]. Up to ~50% loss in the β cell mass has been reported in T2DM patients [115][116][117][118]. Apoptosis and dedifferentiation have been attributed as the main reasons for this substantial decline in the β mass.…”
Section: Pathophysiology Of Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 99%